PENGARUH MONEY ATTITUDE TERHADAP PERILAKU PENGELOLAAN KEUANGAN PRIBADI: PENGETAHUAN DAN FINANCIAL SELF-EFFICACY SEBAGAI MODERASI - Dewi, Ira Annisa Kumala; Rochmawati, Rochmawati (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2020)
The study aims to see how money attitudeaffects on financial management behaviours with financial self-efficacy and knowledge as a moderator variable. Research methods use a quantitative approach. The population chosen for this study is 283 students at accounting education from Universitas Negeri Surabaya. Data collection methods used was tests and questionnaires. Data analysis technique was Structural Equation Modeling (SEM) based component Partial Least Square (PLS) using WarpPLS 6.0 software. The analysis showed that: 1) money attitude impact on private-management behaviour is proven by p-value 0.001 â‰¤ 0.01 and coefficient track of 0.393. 2) Financial knowledgeis not as moderate is proven by the coefficient results of financial knowledge management behaviours by 0.097 with p-value 0.095 (weakly significant) and a coefficient financial attitude towards personal financial management behaviour through financial knowledge -0.050 with p-value 0.251. 3) Financial self-efficacy as a moderator variable is proven well shown by a coefficient results of the financial self-regulation privacy management behaviour of 0.464 with p-value 0.001 (highly significant) and the coefficient financial management measures for personal financial management behaviours through financial self-regulation are -0.143 and p-value 0.026. In conclusion, money attitudehas a positive and significant impact on individual financial management behaviour. Financial knowledge does not moderate the effects of financial attitudes on personal financial management behaviours, while financial self-efficacy moderates the effects of money attitudetowards personal financial management behaviours.